The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.26599/jac.2023.9220730
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-driven BaTiO 3 nanorobots patching immunologic barrier to cure chronic rheumatoid arthritis

Abstract: The disruption and reconstruction of the TREM2 + tissue resident macrophage (TRM) barrier on the surface of synovial lining play a key role in the activation and "remission" of rheumatoid arthritis (RA), which engender the prediction of this immunologic barrier as a potential driver for the achievement of "cure" in RA. However, strategies to promote the reconstruction of this barrier have not been reported, and the effect of patching this barrier remains unidentified. On the other hand, appropriate piezoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In another study, Jiang et al in 2023 developed piezoelectric BTO nanoparticles which can be activated by ultrasound for generating electrical stimulation for reprogramming the macrophage phenotype toward M2 for improving the pro-inflammatory conditions for the treatment of rheumatoid arthritis (RA). 86 The obtained results showed that electrical stimulation resulted in decreases in the levels of FAP-α and TNF-α which altered the macrophage phenotype from M1 to M2.…”
Section: Electrical Stimulation Viamentioning
confidence: 99%
See 4 more Smart Citations
“…In another study, Jiang et al in 2023 developed piezoelectric BTO nanoparticles which can be activated by ultrasound for generating electrical stimulation for reprogramming the macrophage phenotype toward M2 for improving the pro-inflammatory conditions for the treatment of rheumatoid arthritis (RA). 86 The obtained results showed that electrical stimulation resulted in decreases in the levels of FAP-α and TNF-α which altered the macrophage phenotype from M1 to M2.…”
Section: Electrical Stimulation Viamentioning
confidence: 99%
“…In addition, ultrasound activated piezoelectricity generation has also been utilized to tune macrophage behavior for the treatment of inflammatory diseases such as rheumatoid arthritis. , For instance, Li et al in 2023 stimulated piezoelectric nanosheets, Fe/BiOCl NSs, using ultrasound in an in vivo articular inflammation model to study its effect on macrophage polarization . From the results, it was observed that CD80+ macrophages decreased by 12.3% and CD206+ macrophages increased by 3.5%, suggesting a successful M2 polarization.…”
Section: Types Of Electrical Stimulation Sources For Immunomodulationmentioning
confidence: 99%
See 3 more Smart Citations